Risk factors of lymph node metastasis in central region in Papillary thyroid micro carcinoma - Zhao, Xing; Zhao, Mingzhen; Zhang, Gang (Nepalese Journal of Cancer, 2022)
Objective: To investigate the correlation between clinico-pathological features and lymph node metastasis of papillary thyroid microcarcinoma (PTMC). Methods: The clinico-pathological data of 142 cases of papillary thyroid microcarcinoma were collected. The relationship between sex, age, tumor location, multi-focality and cervical lymph node metastasis were analyzed. Results: There was increased rate of lymph node metastasis in male patients with PTMC. There was no significant correlation between age, multifocality and lymph node metastasis. Conclusion: The histological subtypes of PTMC have different clinicopathological characteristics and are important factors for cervical lymph node metastasis. Further evaluation of its histological classification is helpful for clinical treatment strategy.